Absence of co-stimulation and not the intensity of TCR signaling is critical for the induction of T cell unresponsiveness in vivo. - Bachmann, M; Speiser, D; Mak, T; Ohashi, P (1999)
Understanding the mechanisms of T cell activation versus induction of unresponsiveness is of critical importance for the rational modulation of immune responses. Efficient T cell activation is critical for vaccination purposes, while the inhibition of T cell responses is potentially important for the ablation of autoimmune diseases. Modulation of co-stimulation and changing TCR-mediated signaling using altered peptide ligands (APL) have been shown to result in clonal T cell unresponsiveness. This study compares for the first time the efficiency of the two approaches for the induction of CD8+ T cell unresponsiveness in vivo for naive and memory T cells using TCR-transgenic mice. The results demonstrate that inhibition of CD28-mediated co-stimulation in the presence of a strong TCR-mediated signal most efficiently induces T cell unresponsiveness. In contrast, APL that are capable of weak TCR triggering fail to interfere with T cell responsiveness in vivo and are ignored by T cells. Thus, short-term blockage of CD28 during antigenic stimulation rather than the use of APL is the most promising way to actively down-modulate responsiveness of naive CD8+ T cells at least in the particular TCR-transgenic mouse model analyzed in this study.